Development of Adaptive Digital Modules in Integrated Science Course for Natural Education Students - Supriyadi; Ayu Rahayu; Yeni Setyowati; Ilham Handika (Universitas Negeri Semarang, 2025)
Course modules must be adapted to the existing Lesson Plan. In the Integrated Science Course of the Natural Science Education Study Program, Universitas Negeri Semarang, there are already course modules but its need to be adapted to the Lesson Plan in the Odd Semester of 2024/2025. This study aims to develop adaptive digital modules of the Integrated Science course for Science Education students. The research was conducted at the Science Education Study Program, Universitas Negeri Semarang in the Odd Semester of the 2024/2025 Academic Year. The research method used is R&D with Four-D Design. Data collection techniques using questionnaires and observations. Data analysis using quantitative and qualitative analysis. The results of the study show that the Adaptive Digital Modules has been developed according to student characteristics and can be used in lectures.